Artículo 47 de la ley orgánica de discapacidades y su incidencia en el acceso laboral de los periodistas con discapacidad en los medios de comunicación de la ciudad de Quevedo, 2019 - Verdesoto Pinargote, Evelyn Karina (2019)
The present investigative work is presented with the purpose of investigating the incidence of article 47 of the Organic Law of Disability in the labor access of journalists with disabilities in the media of the city of Quevedo, 2019. In order to determine the proposed objective, surveys were applied to the legally registered media of the city of Quevedo, and an interview was conducted with a journalist with a disability who presented physical disability. It was found that there is a low level of inclusion of journalists with disabilities in the media of the Quevedo canton, with 92% of the media surveyed saying that they do not have journalists with any disability working in their environment. barriers to hiring journalists with disabilities are: lack of knowledge about the interaction with people with disabilities in the first place; in second and third place with similar percentages, Infrastructure not adequate in the workplace To solve the problem raised, a workshop on labor integration was developed to promote access for journalists with disabilities in the media of the Quevedo canton, improving compliance and application of Article 47 of the Organic Law on Disability